A New Approach to International Arbitrage Pricing. - Bansal, Ravi; Hsieh, David A; Viswanathan, S (Journal of Finance, 1993)
This paper uses a nonlinear arbitrage-pricing model, a conditional linear model, and an unconditional linear model to price international equities, bonds, and forward currency contracts. Unlike linear models, the nonlinear arbitrage-pricing model requires no restrictions on the payoff space, allowing it to price payoffs of options, forward contracts, and other derivative securities. Only the nonlinear arbitrage-pricing model does an adequate job of explaining the time-series behavior of a cross section of international returns.